Examination of the Nutrient and Water Utilization of Different Corn Genotypes in the Hajdúság - Karancsi, Lajos (Acta Agraria Debreceniensis, 2014)
The research was set up on chernozem soil at the Látókép MÉK research area of the University of Debrecen in Hungary. We examined the following factors of the hybrid P9494, P9578, PR37N01 and PR37M81 in 2013.Yield, yield production per 1 kg fertilizer, water utilization and nutrient reaction. We found that the best yield results were achieved at level N120+PK in case of hybrid P9494 (17 132 kg ha-1) P9578 (16 838 kg ha-1) and PR37N01 (17 476 kg ha-1) and at level N150+PK for hybrid PR37M81 (16 754 kg ha-1). Results of yield per 1 kg NPK studies indicate that the most intense yield growth occurred at level N30+PK compared to the control treatment. This means that yield production per 1 kg NPK was 39.2 kg kg-1 in the case of hybrid P9494, 54.2 kg kg-1 in the case of P9578, 17.6 kg kg-1 for PR37N01 and 44.2 kg kg-1 in the case of PR37M81. After comparing corn hybrids’ water utilization, our conclusion was that the control treatment achieved the worst results in the case of each hybrid (P9494: 20.8 kg mm-1, P9578: 21.0 kg mm-1, PR37N01: 26.2 kg mm-1, PR37M81: 19.5 kg mm-1). For hybrid P9494, P9578 and P37N01, the best water utilization results were measured at level N120+PK (31.5 kg mm-1, 31,0 kg mm-1 and 32.1 kg mm-1), while PR37M81 reached the highest values at level N150+PK (30.8 kg mm-1). We determined the hybrids’ nutrient reaction and its optimum fertilizer values. The best nutrient reaction results were achieved by hybrid PR37N01, while that of hybrid PR37M81 proved to be the weakest.